Readiness For The Implementation Of Digital Technology In Administrative Services In The General And Equipment Sub-Division Of The Social Services Department Of Bengkulu Province: Kesiapan Penerapan Teknologi Digital Pelayanan Administrasi Pada Sub Bagian Umum Dan Perlengkapan Dinas Sosial Provinsi Bengkulu - Rajendra Adnan Sayuti; Edi Darmawi; Henny Aprianty (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This research aims to find out the digital innovation of administrative services in the Subdivision and Social Affairs ofBengkulu Province, the efforts made by the Bengkulu Provincial Social Service General Subdivision and Equipment in overcoming the obstacles of digital administration services for the community, especially parents . This study uses the Qualitative Descriptive method. With data collection techniques in the form of interviews, observations, and documentation. Based on the results of research and discussion on digital technology innovations in the General and Equipment Subdivision of the Bengkulu Provincial Social Service, it can be concluded that the innovation has proven to have a positive impact on administrative services in the General and Equipment Subdivision of the Bengkulu Provincial Social Service even though it still faces challenges, such as limited human resources, lack of knowledge about technology, and lack of public understanding of the technology service system. supporting factor for the success of this innovationlies in the professional performance of employees, and itis verygood to improve the quality of digital technology service innovations in the General and Equipment Subdivision of the Bengkulu Provincial Social Service. Meanwhile, the main inhibiting factors come from limited resources and lack of technological literacy among certain communities.